SIMULATION OF THE MOVEMENT CONTAMINATION OF MANGANESE (MN) & IRON (FE) IN GROUNDWATER AT LANDFILL. XYZ, WEST JAVA. - Kaesmetan, Delvianus
Landfill XYZ is one of the landfill that is operated in West Java, Indonesia and is projected to cease operations in a few next years. The landfill is capable of accommodating a daily waste volume of 6,500-7,000 tons. One of the problems arising from waste is the contamination of the groundwater quality in its vicinity. Through this research, it is expected to understand the hydrogeological conditions, the groundwater flow patterns, and the movement patterns of manganese and iron contaminants in the groundwater, and create a simulation model of the movement of these contaminants at landfill XYZ for the next five years. The simulation model of metal contaminants (manganese and iron) in groundwater is conducted numerically using Visual Modflow based on geological and hydrogeological data. The geological survey includes observations of morphology and lithology (borehole logs and geoelectric surveys). The hydrogeological survey includes measurements of groundwater levels, analysis of groundwater samples, permeability measurements (slug tests), climatological data, and other supporting data such as storativity and dispersivity values. These data are used as initial parameters to build the geometry of the model. The quantitative results of the research consist of a groundwater flow model, with hydro stratigraphic units consisting aquifers and aquicludes. The aquifer is composed of sandstone with a hydraulic conductivity value of 2,274x10-6 m/s obtained from direct field measurements, while the aquiclude is composed of claystone and mudstone with a hydraulic conductivity value of 1,157x10-8 m/s. In the groundwater; manganese, iron, TDS, pH, E.coli microorganisms, nitrate, and nitrite concentrations were found to exceed the standard quality requirements of the Indonesian Ministry of Health Regulation No. 32 of 2017 on Environmental Health Quality Standards and Drinking Water Requirements. Among all the elements that did not meet the standards, a simulation model of the movement of the metal contaminants (manganese and iron) was created. The manganese content in AT-03 was 27.95 mg/liter, and in SP-04 it was 36.69 mg/liter, whereas the manganese standard is only 0.1 mg/liter. Meanwhile, the iron (Fe) content in groundwater was 23.24 mg/liter, whereas the iron standard is 0.2 mg/liter. The values of these metal contents far exceed the standards, highlighting the need for simulations to be used for future monitoring and evaluation. The simulation model of contaminants is created with the aim of determining the extent of dispersion over the next five years. From the 5-year contaminant modeling scenario, the results conclude that the spread of manganese in AT-03 reaches a distance of 390 meters (horizontal) and 34 meters (vertical), while in SP-4 it reaches 444 meters (horizontal) and 33 meters (vertical). As for the spread of iron in SP-4, it reaches a distance of 222 meters (horizontal) and 34 meters (vertical).